The Impacts of Rohingya Refugee Influx on Bangladesh - Hossain, Sazzad (2022)
The Rohingya, a Muslim minority ethnic group in Myanmar, were forcibly displaced to Bangladesh in 2017 on the ground of ethnic cleansing by the military government. This study aims to provide a comprehensive review of the socio-economic impacts of the Rohingya refugee influx on the host community. This paper uses push-pull and realism theories to identify the roots causes of this massive influx to Bangladesh. The study applies a qualitative method to analyze the impact of the Rohingya refugees on the economy of Bangladesh, complemented by a qualitative literature review. The results indicate that rising prices, along with falling wages of low-skilled workers are negatively affecting host communities. Environmental degradation, as well as excessive pressure on already strained infrastructure and public services, are major concerns. Further research is needed to identify other factors that could strengthen the effectiveness of the repatriation.